Analysis of energy storage operation on the power supply side under a high proportion of wind power access based on system dynamics. Issue 1 (1st December 2022) - Huang, Haoyang; Yang, Ying; Yu, Bangdong; Jiang, Leilei; Liu, Zhi; Song, Dongming
Abstract: With the rapid development of renewable energy sources such as wind energy and solar energy in China, structural problems such as wind and light abandonment, system operation imbalance, and insufficient energy supply have arisen in the process of accelerating the energy transformation process. Given the above problems, this paper uses the system dynamics method for modeling. First, the key variables are selected from the perspective of influencing the economic reliability of the power system. Second, the energy storage operation model of the power supply side under the high proportion of wind power access is established, and the impact of new energy access on the system balance and energy storage configuration is explored. Finally, the cost connection of each module body is used to optimize the allocation of energy storage resources, thereby improving the efficiency of the enterprise itself and providing a new idea for the power generation enterprise to participate in the operation and scheduling of the system.